Glucose Homeostasis in Obese Women Is Not Associated to Unacylated Ghrelin Plasma Levels. Issue 15 (June 2020) - Veiga, Luisa; Brito, Miguel; Silva, Carina; Silva-Nunes, José
Introduction: Unacylated ghrelin (UAG) is the major form of circulating ghrelin. Initially considered as a nonfunctional peptide, soon after, UAG has been associated to an insulin sensitizing action and to a negative action on energy balance. The aim of this study was to analyze the association between the serum levels of UAG and glucose metabolism parameters in obese women, independently from eventual influence of anthropometrics. Methods: One hundred lean and 254 obese Caucasian women were studied. Each woman was characterized for anthropometrics, fasting glucose, insulin, HbA1c, and UAG. In addition, obese women were subjected to a classic oral glucose tolerance test (oGTT) to assess glucose and insulin at 120 minutes. Insulin resistance was assessed by the homeostasis model assessment (HOMA-IR). Obese women were classified in 3 glycemic status subgroups (normoglycemia, prediabetes, and diabetes) according to HbA1c and to fasting and oGTT glucose values. Results: In comparison with the lean group, significantly lower levels of UAG were observed in obese women. However, no significant difference was observed through obesity classes I to III. UAG levels were not significantly different among glycemic status subgroups and did not show any association with glucose, insulin, HOMA-IR, or HbA1c. Conclusions: Although anthropometry can influence the level of the unacylated form of ghrelin, UAG plasma levels do not associate to glucose homeostasis parameters.